Comparative study of Ethylene Glycol and Fe3O4-Water on unsteady MHD fluid flow exponentially vertical accelerated plate through porous medium with radiation effect - B. Shankar Goud (Partial Differential Equations in Applied Mathematics)
The problem of unsteady MHD flow of the nanofluids past an exponentially accelerated vertical plate embedded in a permeable medium is investigated. The three fluids are assumed to be electrically conducting water-based nanofluids. Thermal radiation and electromagnetic field impacts are taken into account. The resultant nondimensionalized boundary value problem is solved numerically using the finite difference method used in the procurement numerical results of the governing equations. The comparisons of velocity and temperature fields of Ethylene glycol-water and Fe3O4-Water are presented graphically. The velocity of Ethylene glycol-water is greater than that of Fe3O4-Water. The temperature of Ethylene glycol-water is greater than the temperature of Fe3O4-Water.